INTEGRATED LEARNING BASED ON COMPETENCE IN VOCATIONAL HIGH SCHOOL - Wibowo, Pangarso Ari; Kuat, Tri; Sayuti, Muhammad (Universitas Ahmad Dahlan, 2018)
Education in Vocational High Schools (VHS) aims to equip learners with the attitude, knowledge, and skills to be ready for work, absorbed in the world of work, or entrepreneurship. To fulfill the objective, the competence that must be possessed by the students must be in accordance with the needs in the world of work and in the business world. To fulfill the competence, the learning in VHS must be competency-based. In line with the competency and competency-based learning needs, it also needs an integrated learning between adaptive subjects and productive subjects. Integrated learning is modeled by; (1) conducting curriculum study on basic competence of adaptive subjects, (2) inserting productive basic competency subjects on adaptive subjects. After the integrated learning model is prepared then the learning model applied to the class is a competency-based learning model.